Investigating the Effect of 8 Weeks of Endurance Training on the Levels of Inflammatory Markers (IL-6/TNF-α) and Some Metabolic Parameters in Male Rats with Nonalcoholic Fatty Liver Disease - Vahid Kazemizadeh; Amirabbas Monazzami; Fakhredin Saba; Andrew J McAinch (بهداشت و ایمنی کار)
Introduction: This study aimed to analyze the effects of endurance training (Aerobic) on the levels of inflammatory markers (IL-6/TNF-α) and some metabolic parameters in male rats with non-alcoholic fatty liver disease to investigate the feasibility of using exercise training to reduce inflammation. Material and Methods: A total of 44 Wistar rats were randomly assigned into two groups: (I) standard diet group of 22 rats and (II) high-fat diet group with 22 rats supplemented with free access to fructose water. After 17 weeks, two rats from each group were sacrificed, and liver tissue was collected for hematoxylin-eosin staining. Subsequently, the remaining 20 rats in the (I) group were divided into a training group (T) and a control group (C). The 20 rats in the (II) group supplemented with fructose water were divided into a fatty liver group (FL) and a fatty liver + training group (FL+T), each comprising ten rats. In the next phase, the T-groups underwent an eight-week endurance training intervention. Then, IL-6, TNF-α, glucose, insulin, insulin resistance and sensitivity levels were measured. Results: The results of the present study showed that as a result of a high-fat diet with liquid fructose in HFD+HF group rats, non-alcoholic fatty liver disease (NAFLD) with complications such as a significant increase in the levels of IL-6 and TNF-α, Hepatic dysfunction, and metabolic parameters were disturbed (p<0.001). However, endurance training improved most of these complications by reversing the disease process (p<0.001). Conclusion: According to the results of the present study, it can be concluded that the improvement of inflammatory markers, liver dysfunction, and metabolic parameters through endurance training is one of the key mechanisms of exercise in the treatment of NAFLD, the consequences of which may show the importance of endurance training in treatment of NAFLD highlights.